Autentikasi G.dulcis terhadap Adulterasi G.Mangostana dengan Metode Spektrofotometri Kombinasi Kemometrik - Samsul Hadi; Kunti Nastiti (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Garcinia is a genus consisting of various species that engage in diverse activities. The two garcinia species that have been studied are G. dulcis and G. mangostana. Fruit extracts from the pericarp of both species have antioxidant, antibacterial, anti-hyperlipidemic, and anti-diabetic activity. However, the activities of these two species vary, so authentication of one species is necessary. This study aims to authenticate G. dulcis in a mixture of G. dulcis and G. mangostana. This research uses a combination of the spectrophotometric method and chemometrics. The equipment used is UV-vis spectrophotometry, and data analysis uses PLSR. The research results show that at a wavelength area of 246.77–224.46 nm, the normal model RMSEC is 3.75 and R2 is 0.99, and the wavelength 300.2-256.56 nm of the second derivatization RMSEC is 3.21 and R2 is 0.9956. Based on the data obtained, it can be concluded that the 2nd derivatization model at a wavelength of 300.2-256.56 nm is the best model for authenticating G.dulcis against G.mangostana because it has the lowest RMSE and the highest R2 qualitatively but has not been able to quantify the difference.